ANALISIS ASPEK ERGONOMI PEKERJA BAGIAN SORTASI AKHIRPADA PENGOLAHAN KOPI ROBUSTA SECARA SEMI BASAH (Studi Kasus PT. J. A. Wattie Perkebunan Durjo Jember) - Andrew Setiawan R; I B Suryaningrat; Isman Hadi Subhan (Agroindustrial Technology, University of Trunojoyo Madura, 2012)
The research objective is evaluating the convenience of the sorting condition in terms of aspects concerning the use of anthropometry include the comfort of a chair, to evaluate the working environment (temperature and humidity of the room work as well as noise) and provide an alternative design of chairs and tables by the method of anthropometry. This research used 30 respondents who had been sampled. The research was limited to observations of temperature, humidity, noise and anthropometric include seat height, height shoulders, wide hips, knee height, popliteal height, buttock - popliteal, shoulder width, height and arm reach. The results showed that the temperature and humidity of the room was still not optimal noise intensity as well as some parts of the production of more than Limit Value. Subjective complaints occurred in almost all parts of the body of workers. Complaints caused by the design of chairs and tables that are less ergonomic and environmental conditions are less than optimal. The size of the table after redesigning the table height 80 cm, width 70 cm and length of the table table 195 cm while the size of a chair after redesigning the high chair (without backrest) 46 cm, 100 cm wide backrest and cushion length and 120 cm high backrest by 54 cm. Alternative solution given is to redesign the tables and chairs based on data antropomerti workers so as to create a means by which ergonomic and improvement of environmental conditions.